Avaliação da aprendizagem na educação física da rede de ensino de Miracema do Tocantins - Pinto, Welma Coelho (Universidade Federal do Tocantins, 2021)
This work aimed to understand the evaluative practices of Physical Education teachers in the teaching network of Miracema do Tocantins, who work in the final phase (elementary and high school) we have seen that evaluation has been a problem for teachers in this discipline, because their role is fundamental in the pedagogical practice of teachers at school, its function is diagnostic, procedural and summative and contributes to teacher decision making in order to contribute to student learning. To make this research possible, we used the case study method that, according to Gil, (2010), is used as a more adequate design for the investigation of a contemporary phenomenon, within a real context. The instrument used in this study was a structured questionnaire applied to teachers with training in Physical Education from the Miracema teaching network. The first chapter reviews the main studies mapped in the journals Movimento, Pensar a Prática e Motrivivência in the last three years (2015 and 2018). In the next chapter, we covered the answers given by the teachers through the questionnaire, which talks about the formation of the teacher, which instruments he uses to evaluate, which is more relevant when evaluating. Finally, we understand that it was possible, through the questionnaire, to identify which guidelines the teachers received throughout their training and performance on the evaluation in physical education and to identify which evaluative practices produced by teachers with training in physical education.